Biocompatibility of Nanoparticles: Hematological Effects of Gold Nanorods on Erythrocytes: Hemolysis and Hemoglobin Conformational and Functional Changes (Adv. Sci. 12/2017). Issue 12 (20th December 2017) - Zhao, Xingchen; Lu, Dawei; Liu, Qian S.; Li, Yiling; Feng, Rui; Hao, Fang; Qu, Guangbo; Zhou, Qunfang; Jiang, Guibin
Abstract : In article 1700296, Qunfang Zhou and co‐workers report the hemocompatibility of gold nanorods (GNRs). In contrast to negatively charged GNRs, positively charged GNRs (C‐GNRs) induce instant hemolysis. After cellular encapsulation, the GNRs are found to bind with hemoglobin and to induce conformational and functional changes in the protein. This demonstrates that surface modification holds great promise as an approach to improve the biocompatibility of GNRs for clinical use.